1992
DOI: 10.1007/s0054020060277
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between ORG9426 and other non-depolarizing neuromuscular blocking agents in ratsin vivo

Abstract: In this study, combined neuromuscular blocking effects of ORG9426 with other non-depolarizing neuromuscular blocking agents were investigated. About 20% steady state neuromuscular block was established by a continuous infusion of one of 6 neuromuscular blocking agents (ORG9426, vecuronium, pancuronium, pipecuronium, d-tubocurarine and metocurine). Then 1/7 of the ED50 of ORG9426 or one of other neuromuscular blocking agents was administered in a single injection, and the increase in the neuromuscular block was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…ere are no earlier studies using this combination in conditions simulating clinical intubation. Golpariaini and colleagues, on phrenic-nervehemi-diaphragm preparations of male Sprague-Dawley rats, constructed isobolograms from the IC50 values and shown that ORG9426 potentiates pancuronium [25,26]. However, Naguib by the isobolographic analysis observed additive interaction between rocuronium and pancuronium [27].…”
Section: Discussionmentioning
confidence: 99%
“…ere are no earlier studies using this combination in conditions simulating clinical intubation. Golpariaini and colleagues, on phrenic-nervehemi-diaphragm preparations of male Sprague-Dawley rats, constructed isobolograms from the IC50 values and shown that ORG9426 potentiates pancuronium [25,26]. However, Naguib by the isobolographic analysis observed additive interaction between rocuronium and pancuronium [27].…”
Section: Discussionmentioning
confidence: 99%